An estimation’s method at most attainable of length path in fixed broadband wireless access: engineering-maintenance of the calculation - Panteleev, Victor V. (Видавництво Львівської політехніки, 2012)
Methods of the engineering evaluation at most attainable lengths of the part in fixed radio systems with detailed conclusion of the equation of distance is offered. It’s discussed technological spare on expected Noise Margin (NM) on base 5-th balls scale criterion Mean Opinion Score (MOS) Quality-of-Service (QoS) of digital telecommunications under subjective perception Quality-of-Experience (QoE).
Keywords: Access Network Transport (ANT); Equations Part & Span in Broadband Wireless Access (BWA)